ANALISIS KADAR ASAM URAT PADA PASIEN KARSINOMA MAMMA - Susi Sevianty; Uleng Bahrun; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
In malignancy cases, an increase of uric acid level is often observed after therapy (Tumor Lysis Syndrome), but some studies also indicated an increase before therapy which is related to a refusal reaction against tumor, and specific only for certain malignancy cases.Carsinoma mammae is the second most common malignancy among women in Indonesia, so that studying the phenomenon occurredin carcinoma mammae including uric acid level are expected to provide insight in management of carcinoma mammae. A longitudinalstudy was conducted by collecting secondary data from medical record of carcinoma mammae patients in Wahidin SudirohusodoHospital for period of July 2007–June 2008. Data were analyzed by using Wilcoxon Signed Rank Test with alpha 0.05. 12 of subjectsare considered eligible for study criteria, with the age ranging from 28–60 years old. In generally, uric acid level determined beforeand after chemotherapy showed a level in normal range, except for 3 samples before therapy and 3 different samples after therapyshowed a level more than 5.7 mg/dL. Statistic result showed mean uric acid level before chemotherapy was 4.508 ± 1.2566 mg/dL andafter chemotherapy was 5.025 ± 1.3240 mg/dL (p = 0.16). Increased of uric acid level is not significant level was found in serum ofcarcinoma mammae before and after chemotherapy.